Posttraumatic biloma formation - Diagnosis and management - Teles Filho, Ricardo Vieira; Abe, Guilherme de Matos (Clinical and Biomedical Research, 2019)
A 25-year-old male patient sustained complex blunt hepatic trauma after abdominal crush injury by an object heavier than 100 kg. He had liver laceration, pulmonary contusion and hemothorax. Exploratory laparotomy was performed, followed by urgent hepatorrhaphy. After 3 weeks, the patient presented with sharp pain and discomfort in the upper right quadrant and abdominal distension associated with intense nausea. An abdominal ultrasound (US) demonstrated voluminous liver cyst formation. Abdominal computed tomography (CT) was performed and showed voluminous intrahepatic loculated fluid collection (Figure 1). Magnetic resonance cholangiopancreatography (MRCP) was then performed (Figure 2) to exclude cystic lesion and to establish the actual location of the lesion; it demonstrated extra- and intrahepatic biliary tree injury (Figure 3). Abdominal drainage of the collection was performed by ultrasound-guided percutaneous drainage, collecting about 1,500 mL of bile, and confirmed the diagnosis of biloma. The procedure had no complications, and the patient was discharged with an abdominal tube draining biliary secretion, which was removed after 3 weeks. After two months, follow-up CT demonstrated the resolution of the case. The patient was then followed every two months for the following six months after the drainage procedure, with tomographic studies demonstrating no new biliary leak. Hence, he was finally discharged in good medical condition. Keywords: Biloma; biliary leak; liver trauma